(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cloud computing is an aggressive concept to solve different types of real time data outsourcing applications. Resource utilization is one of main concept in outsource services into different users via virtual machines in distributed environment. Optimize resource provisioning and utilization is the main aggressive concept to share different services to different users in different scenarios. Stochastic based resource provisioning prediction management (SRPPM) based on linear regression is one of the optimized approach to satisfy resource provisioning and utilization in distributed computing. Multi user multi servers with multi resource provisioning is still a challenging task in cloud computing. In this document, to propose Virtual and Multiplexer based Optimal Resource Provisioning (VMORP) approach to handle multi user resource utilization in distribution environment. Our proposed approach follows resource provisioning in two different stages i.e reservation and on-demand stages to optimize resources for different users with different services. Probability service function is used in VMORP approach to handle optimized resource provisioning in distributed environment. Our experimental results show efficient resource provisioning with different users in cloud computing.